NBR1 is involved in selective pexophagy in filamentous ascomycetes and can be functionally replaced by a tagged version of its human homolog. Issue 1 (2nd January 2019) - Werner, Antonia; Herzog, Britta; Voigt, Oliver; Valerius, Oliver; Braus, Gerhard H.; Pöggeler, Stefanie
ABSTRACT: Macroautophagy/autophagy is a conserved degradation process in eukaryotic cells involving the sequestration of proteins and organelles within double-membrane vesicles termed autophagosomes. In filamentous fungi, its main purposes are the regulation of starvation adaptation and developmental processes. In contrast to nonselective bulk autophagy, selective autophagy is characterized by cargo receptors, which bind specific cargos such as superfluous organelles, damaged or harmful proteins, or microbes, and target them for autophagic degradation. Herein, using the core autophagy protein ATG8 as bait, GFP-Trap analysis followed by liquid chromatography mass spectrometry (LC/MS) identified a putative homolog of the human autophagy cargo receptor NBR1 (NBR1, autophagy cargo receptor) in the filamentous ascomycete Sordaria macrospora (Sm). Fluorescence microscopy revealed that SmNBR1 colocalizes with SmATG8 at autophagosome-like structures and in the lumen of vacuoles. Delivery of SmNBR1 to the vacuoles requires SmATG8. Both proteins interact in an LC3 interacting region (LIR)-dependent manner. Deletion of Smnbr1 leads to impaired vegetative growth under starvation conditions and reduced sexual spore production under non-starvation conditions. The human NBR1 homolog partially rescues the phenotypic defects of the fungal Smnbr1 deletion mutant. The Smnbr1 mutant can neither use fatty acids as a sole carbon source nor form fruiting bodies under oxidative stress conditions. Fluorescence microscopy revealed that degradation of a peroxisomal reporter protein is impaired in the Smnbr1 deletion mutant. Thus, SmNBR1 is a cargo receptor for pexophagy in filamentous ascomycetes.